2023
DOI: 10.3390/app13095612
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Strategy Improved Flamingo Search Algorithm for Global Optimization

Abstract: To overcome the limitations of the Flamingo Search Algorithm (FSA), such as a tendency to converge on local optima and improve solution accuracy, we present an improved algorithm known as the Multi-Strategy Improved Flamingo Search Algorithm (IFSA). The IFSA utilizes a cube chaotic mapping strategy to generate initial populations, which enhances the quality of the initial solution set. Moreover, the information feedback model strategy is improved to dynamically adjust the model based on the current fitness val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This technique starts with creating an even or In the ISFO algorithm, opposition-based learning (OBL) was integrated, which is an optimizer algorithm which enhances the capability of intelligent algorithms to escape from local optimum [20]. Random OBL (ROBL) is an upgraded form of OBL.…”
Section: Optimal Key Selection Using Isfo Algorithmmentioning
confidence: 99%
“…This technique starts with creating an even or In the ISFO algorithm, opposition-based learning (OBL) was integrated, which is an optimizer algorithm which enhances the capability of intelligent algorithms to escape from local optimum [20]. Random OBL (ROBL) is an upgraded form of OBL.…”
Section: Optimal Key Selection Using Isfo Algorithmmentioning
confidence: 99%
“…In the IFBFFA algorithm, an information feedback mode was introduced to integrate helpful data from prior iterations into the update mechanism, which results in a considerable development in the solution quality (Jiang et al, 2023).…”
Section: Optimal Feature Extraction Modulementioning
confidence: 99%
“…These algorithms can compensate for the shortcomings of the original algorithms by integrating new strategies or the advantages of other algorithms to achieve better optimization results. For example, Hu et al suggested an enhanced Jellyfish Optimization Algorithm (EJS) with multiple strategies, and its exceptional efficacy was confirmed through various test functions and practical engineering uses [27]; Li and others suggested a superior dung beetle optimization algorithm (EDBO) suitable for engineering uses, and its efficiency was assessed with the CEC2017 function set, revealing EDBO's robust optimization stability and precision [28]; Zheng and colleagues suggested an advanced multi-strategy African Vulture Optimization Algorithm (EAVOA), which was utilized in multi-layered perceptual classification experiments using XOR and cancer data, demonstrating its superiority over alternative approaches [29]; Jiang and colleagues suggested an enhanced multi-strategy Flamingo Search Algorithm (IFSA), with experimental confirmation of its superior convergence precision and detection ability [30]; Liu and colleagues suggested an algorithm for quilt swarming that merges a multi-strategy approach with hybrid Harris optimization (MSHHOTSA), and confirmed through experiments that MSHHOTSA outperforms BOA, GWO, MVO, HHO, TSA, ASO, and WOA in terms of local convergence, overall exploration capability, resilience, and broad applicability [31]; Song and others introduced an adaptive particle swarm optimization algorithm (APSO/DU) with multiple strategies, opting for an actual MSV portfolio optimization challenge. The findings indicated that the APSO/DU algorithm excels in convergence precision and speed, successfully identifying the stock portfolio with minimal risk while maintaining equivalent returns [32].…”
Section: Introductionmentioning
confidence: 99%